STRATEGI PENGUATAN SISTEM PERLINDUNGAN HUKUM BAGI KORBAN PELECEHAN ANAK - Nurul Cholafina Dela Cantika; Muhamad Chaidar (Fakultas Ilmu Sosial dan Humaniora, 2025)
Children are a vulnerable group that requires special protection, especially in cases of abuse. This research aims to identify strategies for strengthening the legal protection system for victims of child . The research method used is a normative juridical approach with analysis of applicable regulations and case studies of their implementation. The research results show that there are weaknesses in the implementation of laws and regulations, a lack of special training for law enforcers, and a lack of access for victims to assistance services. Recommended strategies include strengthening regulations through harmonization of national laws, providing child sensitivity-based training for law enforcement officers, and establishing integrated service centers involving psychologists, legal assistants and local communities. The implementation of this strategy is expected to increase effective and fair legal protection for victims of child abuse.